A novel triangular wave quadrature oscillator without passive components for sinusoidal pulse width modulation DC-AC power conversion - Theodora Valerie; Tole Sutikno; Joni Welman Simatupang; Dodi Garinto; Harki Apri Yanto (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this study, a low-cost quadrature triangle oscillator using a voltage-controlled closed-loop dual operational amplifier (Op-Amp) architecture is proposed. Unlike other typical designs, this oscillator does not require any passive components. The use of an Op-Amp-based circuit is attractive for a triangle oscillator because it is more cost-effective than a microcontroller-based solution. This is especially true for sinusoidal pulse width modulation (SPWM) DC-AC power conversion applications. The slew-rate restriction of an Op-Amp is a useful characteristic for producing a triangle waveform when seen from the perspective of wave shaping techniques. The MC4558 and the JRC4558D are two examples of dual Op-Amps that are evaluated, contrasted, and described in this article. At supply voltages of +7 V and -7 V, the suggested quadrature triangle oscillator that uses Op-Amps MC4558 and JRC4558D has the same oscillation frequency, which is 63 kHz, as demonstrated by simulation and experimental data. The frequency stability is estimated to be around 0.23%. In addition, the findings from the experiment demonstrate that the proposed oscillator is a practical solution for the SPWM DC-AC power conversion application.